Effects of local platelet-rich plasma injection on the rate of orthodontic tooth movement in a rat model: A histomorphometric study - YARAT, AYŞEN (MOSBY-ELSEVIER, 2017)
Introduction: The aims of this study were to determine the effects of different concentrations of platelet-rich plasma (PRP) on alveolar bone density and orthodontic tooth movement. Methods: Seventy-six rats were divided into 2 groups: a moderate concentration PRP injection group (n = 38) and a high concentration PRP injection group (n = 38). In each group, 5 time points were studied: 3, 7, 14, 21, and 60 days. Before orthodontic mesialization of the maxillary first molars, moderate and high concentrations of PRP were injected on the right sides of the molar buccal sulcus, and the left sides served as the controls. Tooth movements were measured on 3-dimensional digital models. Alveolar bone volume density and osteoclastic activity in the first molar intraradicular areas were evaluated by histomorphometric analysis. Results: Alveolar bone density was decreased in the experimental groups compared with the control groups (P = 0.0001) at 3, 7, 14, and 21 days. On day 3, osteoclastic activity of the experimental groups was higher than that of the controls (P = 0.044, P = 0.0001). On day 21, the amounts of tooth movement in the high-concentration experimental group were 1.7 times greater than in the high-concentration control group and 1.4 times greater than in the moderate-concentration experimental group (P = 0.001). On day 60, alveolar bone density increased to the original levels in all groups. Conclusions: Injection of both moderate and high concentrations of PRP may accelerate orthodontic tooth movement by decreasing alveolar bone density on paradental tissues by enhancing osteoclastic activity in a transient way.
Keywords: SELECTIVE ALVEOLAR DECORTICATION; GROWTH-FACTOR; GENE-TRANSFER; IN-VITRO; BONE; ENHANCEMENT; DEFECTS